Government-driven university-industry linkages in an emerging country: the case of China - Su, D.; Zhou, Dayong; Liu, C.; Kong, L. (Emerald, 2015)
Purpose – The purpose of this paper is to analyze and summarize the development of science and technology (S & T) policies in China from a government-driven perspective in chronological order. To develop knowledge-based economy, China enacts a range of S & T policies since “Reform and Open Policy” started in 1978. Furthermore, it investigates the overall effects of these S & T policies on university-industry linkages (UILs). Design/methodology/approach – This paper conducts an analysis framework of S & T policies in historical sequence to explain how government drives UILs to stimulate technological progress and economic growth in China. Findings – More than a site for high-quality workforce education and knowledge spread, universities as an important part of national innovation are required to participate in economic activities. Considering that most Chinese universities are national, S & T policies with particular regard to university technology transfer would be more important and essential. This research finds that S & T policies enacted by government have made critical contributions to UILs in economic transition period, such as improving academic faculty, enhancing university–industry collaborations and supporting university spin-off formation. The experiences of China suggest that government should enact more effective S & T policies in the knowledge-based economy era. Practical implications – First, universities need to educate high-level human resources that are important for economic growth and social development. Second, universities need to engage in R & D activities and enhance their collaboration with industries, such as consulting services, research contracts with industry, patent licensing and other general knowledge commercial mechanisms. Third, universities also can directly transfer commercial knowledge to start up new businesses by itself or in partnership with industrial sectors. Without doubt, a series of S & T policies or programs enacted by China’s government to drive entrepreneurship continuously played critical role in the UILs over the past 26 years. Originality/value – This paper is a pioneering work on how S & T policies enacted by government drive UILs to stimulate technological progress in transitional China.